Gender and Roots Tubers and Bananas Seed Systems: a literature review - Mudege, Netsayi N.; Walsh, S. (International Potato Center, 2016)
Using literature review this paper seeks to discuss gender integration into design and understanding of seed system interventions in roots, tubers, and bananas (RTB) crops. It focuses mainly on offering a critique of the multi-stakeholder framework for intervening in RTB seed systems, and offering suggestions on how to integrate gender into the framework. The paper emphasizes the importance of understanding how social structures and informal rules such as gender and cultural norms determine participation in, and benefit from, seed systems. In addition, existing social systems and cultural norms may govern or influence how the different stakeholders-including scientists, extension workers, and practitioners among nongovernmental organizations (NGOs)-act and relate with male and female farmers. Men and women may face different constraints and opportunities to participate meaningfully in seed systems, and these different constraints need to be understood in order to define seed systems interventions that can meet their needs. They may also have different perceptions about quality. As a result, seed system interventions also need to carefully examine how the different stakeholders in the seed system relate with farmers and whether gender biases filter into interactions disadvantaging women over men.